P-42 Location analysis of healthy sport programs and their reachability – services for the adult public and their health care in rural areas. (18th November 2016) - Behrens, K; Weippert, M; Behrens, M; Lübke, J; Klinger, R
Abstract : Background: Physical inactivity is an independent risk factor for emergence and progression of chronic diseases. With regard to the negative consequences of physical inactivity, great efforts have been made to increase the physical activity among all age groups. Sport associations and statutory health insurances have therefore established the use of adequate instruments to support the process of "healthy ageing" (Guide of Prevention, §§ 20 und 20a SGB V). In this context, we investigated the healthcare system coverage of primary prevention sport offers (PS) in Westmecklenburg/GER. Methods: Using ArcGIs (Fa. ESRI) we analysed several locations in the region of Westmecklenburg/GER and their reachability in detail. We developed cartographic data on the reachability by car and by public transport (ÖPNV) at different times of day. At the time of analysis (2013) a population of 474, 005 inhabitants in Westmecklenburg/GER has been taken as a basis. To assess the quality of the public transport, accessibility was evaluated, when people have to leave the house at the latest to reach a sport location by public transport on time. On the way back, the earliest possible arrival time at home was determined when the route starts at the sport location. The travel times reflect the duration of the journey, including walking, waiting and transfer times. In general, for social and medical infrastructure, a maximum travel time of 30 min by public transport is acceptable (BMVI, 2015). For the accessibility by car, a period of 20 min is defined as reasonable travel time (BMVI, 2015). Result: The ÖPNV reachability analysis showed difficulty to fairly reach the offered PS in this region. 50, 5 % of the population need more than 60 min and 25, 4 % need more than 90 min driving time to use a sport offer in the afternoon hours. Using the offered programs in the evening hours is also difficult: 31, 1 % of the Westmecklenburg/GER population need more than two hours for the way back home (Figure 1 ). In case that any sport offers were available, major cities of Westmecklenburg/GER and its immediate surrounding provided an overall good ÖPNV and car reachability (Figure 2 ). Discussion: The results underline the necessity to further extend PS-offers. Both urban as well as rural areas lack a sufficient quantity of PS-offers. For health care in rural areas, it will be necessary in the future, not only to ensure a balanced distribution of physicians, but also the reachability by all health stakeholders. To establish permanent health sport offers, the establishment of regional networks should be promoted. Currently, sports clubs have an underestimated health potential which should be used. Acknowledgment: The project was supported by the Federal Institute for Building, Urban Affairs and Spatial Development (BBSR). References: Adler G, v.d. Knesebeck J-H. Ärztemangel und Ärztebedarf in Deutschland? Bundesgesundheitsblatt – Gesundheitsforsch – Gesundheitsschutz 2011;54 :228–37. Available from: http://dx.doi.org/10.1007/s00103-010-1208-7 Greß S, Stegmüller K. Gesundheitliche Versorgung in Stadt und Land – Ein Zukunftskonzept. Friedrich-Ebert-Stiftung Hessen (Wiesbaden) 2011 Kuhlmey A. Versorgungsforschung zur angemessenen Gesundheitsversorgung im Alter. Bundesgesundheitsblatt – Gesundheitsforsch – Gesundheitsschutz 2011;54 :915–21. Cirkel M, Juchelka R. Gesundheit und Mobilität im Alter. Public Health Forum 2007: 24–26. Giesel F, Köhler K, Nowossadeck E. Alt und immobil auf dem Land? Mobilitätseinschränkungen älterer Menschen vor dem Hintergrund einer zunehmend problematischen Gesundheitsversorgung in ländlichen Regionen. Bundesgesundheitsblatt – Gesundheitsforsch – Gesundheitsschutz 2013;56 :1418–1424. Bundesministerium für Verkehr und digitale Infrastruktur (BMVI). Kennzahlen in der Daseinsvorsorge. 2015. Available from: http://nbn-resolving.de/urn:nbn:de:101:1-2015042703